EUROPEAN ASSET MANAGEMENT STUDY 2024: REMAINING CAUTIOUS DESPITE MARKET GROWTH (Лучшие интеллектуальные исследования, 2024)
After geopolitical upheavals, especially the implications of Russia’s attack on Ukraine, led to a decline in global assets under management (AUM) in 2022, the European asset management industry saw a trend reversal in 2023: global AUM growth regained speed and the market grew by around 9% Despite this upswing, however, market growth alone is no reason to sit back – lower revenues , cost pressure, technological disruptions and a rise in geopolitical tensions are posing enormous challenges for asset managers after a decade of an upward momentum.In our European Asset Management Study 2024, we have once again analyzed recent developments of European asset managers. On the one hand, we shed light on current trends and their impact on the future of asset management, and on the other hand we identify unused efficiency levers and key areas in which there is an urgent need for action to ensure competitiveness.